INNOVATIVE METHODS IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The landscape of teaching Russian as a foreign language is rapidly evolving due to the integration of innovative pedagogical strategies and digital technologies. This study examines the effectiveness of multimedia tools, communicative language teaching, interactive tasks, and emerging technologies such as artificial intelligence and virtual reality in enhancing student engagement and language proficiency. Conducted among university-level learners over one semester, the research compares outcomes between traditional and innovative instructional methods. Findings reveal that students exposed to innovative approaches exhibit significant improvement in speaking and listening skills, heightened motivation, and increased classroom participation. The study highlights the critical need to modernize Russian language instruction to meet the communicative and cultural demands of contemporary learners.